Diversity from nature to culture: exploring the Qur’anic perspective of diversity in existence - Solihu, Abdul Kabir Hussain (2015)
Diversity is a common characteristic of the natural world. It has made life on earth habitable and nature resourceful and from which humans derive great strength and happiness. Diversity is one of the main factors that make one animal species prey on another. Nevertheless, such diversity does not lead to the war of all against all in the wildlife but to a cosmic takāful (a mutual cooperation and symbiotic relation). Human culture also exhibits diversity. Humans are diverse in faces and faiths. As indicated in the Qur’an, their diversity is not meant to be a source of conflict and confrontation but a springboard for cooperation and mutual support. The Qur’an draws attention to the diversity in the natural world as well as in human communities and considers it as part of grand divine design in existence. Alwān (colours) ikhtilāf (differences) as well as shu‘ūb (nations) and qabā’il (tribes) are some of the Qur’anic key concepts identifying diversity in flora and fauna as well as among human communities. Drawing on these concepts, this study explores the Qur’anic account of diversity in the natural world as well as in human cultural manifestations in attempt to identify the nature of values associated with diversity in nature and culture.